On the use of a powder rheometer to characterize the powder flowability at low consolidation with torque resistances. Issue 11 (2nd September 2017) - Salehi, Hamid; Barletta, Diego; Poletto, Massimo; Schütz, Denis; Romirer, Richard
Abstract : The Anton Paar Powder Cell was used to measure the torque necessary to rotate an impeller in beds of glass beads, sand and alumina powders aerated between no aeration to the minimum for fluidization. Measured torque values depend on the material tested, on the air flow rate applied, on the impeller depth and on the height of the impeller blade. The effect of the impeller depth is linear for low impeller depth and is less than linear at high depth values. A model was developed for the interpretation of the experimental results based on the idea that the material is shearing on the surface described by the impeller rotation. The model allows to estimate an effectiveness of the impeller in the torque determination and also to predict the torque for the impeller at the at deepest positions at which the wall effects have to be considered. © 2017 American Institute of Chemical Engineers AIChE J, 2017